Model Classification Of Nominal Value And The Original Of IDR Money By Applying Evolutionary Neural Network - Al-Khowarizmi Al-Khowarizmi (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2020)
Indonesian Rupiah (IDR) banknotes have unique characteristics that distinguish them from one another, both in the form of numbers, zeros and background images. This pattern of each type of banknote will be modeled in order to test the nominal value and authenticity of IDR, so as to be able to distinguish not only IDR banknotes but also other denominations. Evolutionary Neural Network is the development of the concept of evolution to get a neural network (NN) using genetic algorithms (GA). In this paper the application of evolutionary neural networks with less input is able to have a better success rate in object recognition, because the parameters for producing neural networks are far better